(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, on the basis of studying and researching the social and philosophical aspects of spiritual culture, raising the spiritual culture of young people, self-awareness, self-reformation, in its heart Goodness, humanity, nationalism, patriotism, appreciation of our national spiritual heritage, and the formation of a person are discussed.